In vitro and in vivo effects of clove on pro-inflammatory cytokines production by macrophages - Rodrigues, T. G. [UNESP]; Fernandes, A. [UNESP]; Sousa, J. P. B.; Bastos, J. K.; Sforcin, J. M. [UNESP] (Taylor & Francis Ltd, 2009)
Biological properties of clove have been reported, but little is known about its effect on the immune system. This work was aimed to investigate the effect in vivo of a water-soluble part of hydroalcoholic extract of clove on pro-inflammatory cytokines (IL-1 and IL-6) production by macrophages of BALB/c mice. The action of the essential oil of clove on the production of these cytokines macrophages was also investigated in vitro. The chemical compositions of the extract and of the oil were also investigated. Treatment of mice with water extract of clove was found to inhibit macrophages to produce both IL-1 and IL-6. The essential oil of clove also inhibited the production of these cytokines in vitro. Eugenol was found to be the major component of the clove extract and essential oil, and probably is the causative agent of cytokine inhibition. Taken together, these data suggest an anti-inflammatory action of this spice.
Keywords: clove; essential oil; macrophages; cytokines